2015
DOI: 10.1590/s1984-29612015037
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular diagnosis of Pseudoterranova decipiens (sensu stricto) (Anisakidae) in imported cod sold in Brazil

Abstract: An anisakid nematode larva found in cod sold in the state of Minas Gerais, Brazil was studied by light and scanning electron microscopy and by a molecular approach. Mitochondrial cytochrome c-oxidase subunit 2 (mtDNA cox-2), 28S rRNA and ITS1, 5.8S and ITS2 regions were amplified using the polymerase chain reaction and sequenced to evaluate the phylogenetic relationships of the larva. The genetic profile confirmed that this larva belongs to the species Pseudoterranova decipiens (sensu stricto). This is the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
1
3
0
5
Order By: Relevance
“…(L 3 ) specimens possessed a dorsal lip bearing a pair of double papillae, two ventrolateral lips, a tiny boring tooth between the ventrolateral lips, an excretory pore at the base of the ventrolateral lips, a long ventriculus, absent ventricular appendix, intestinal cecum and a tail with a mucron, which were in agreement with the description of P. decipiens (Krabbe, 1878) (L 3 ) collected from Gadus morhua L., 1758 fillets marketed in Nova Scotia, Canada and Brazil, Thrysites atun (Euphrasen, 1791) from New Zealand and Trigla lucerna L., 1758, from the Mediterranean Sea, France (MCCLELLAND, 1980;HURST, 1984;PETTER and MAILLARD, 1988;MAFRA et al, 2015). Morphometrically, specimens of the present study had a body size approximately three times smaller than those reported by the aforementioned authors.…”
Section: Resultssupporting
confidence: 86%
“…(L 3 ) specimens possessed a dorsal lip bearing a pair of double papillae, two ventrolateral lips, a tiny boring tooth between the ventrolateral lips, an excretory pore at the base of the ventrolateral lips, a long ventriculus, absent ventricular appendix, intestinal cecum and a tail with a mucron, which were in agreement with the description of P. decipiens (Krabbe, 1878) (L 3 ) collected from Gadus morhua L., 1758 fillets marketed in Nova Scotia, Canada and Brazil, Thrysites atun (Euphrasen, 1791) from New Zealand and Trigla lucerna L., 1758, from the Mediterranean Sea, France (MCCLELLAND, 1980;HURST, 1984;PETTER and MAILLARD, 1988;MAFRA et al, 2015). Morphometrically, specimens of the present study had a body size approximately three times smaller than those reported by the aforementioned authors.…”
Section: Resultssupporting
confidence: 86%
“…(2015, 2016) and Mafra et al . (2015) have demonstrated the importance of molecular data for adequate diagnosis.…”
Section: Taxonomy and Systematics Of The Helminths Parasitic In Fish mentioning
confidence: 99%
“…In the UFRRJ, research in the Laboratory of Fish Parasitology has focused on nematodes (Vieira et al ., 2015), besides other taxa (Paschoal et al ., 2016), including recent insights using an integrated taxonomic approach (Pereira et al ., 2015a, b). Research by some groups from FIOCRUZ has dealt with the taxonomy of several helminth taxa (Justo & Kohn, 2012; Leão et al ., 2015), including molecular characterization and diagnosis (Borges et al ., 2015; Mafra et al ., 2015). Finally, the Laboratory of Evolutionary Helminthology from USP includes a productive group focusing on the taxonomy of cestodes parasitic in Chondrichthyes (Marques et al ., 2012; Marques & Reyda, 2015).…”
Section: Current Research Groups and Their Geographic Distributionmentioning
confidence: 99%
“…Results of the morphological comparison confirm the same species affiliation. However the obtained partial 18S rDNA gene was also compared to literature data and similarities with gene sequence of Pseudoterranova decipiens were found ( Mafra et al, 2015 ). Both species of nematodes belong to the suborder Spirurina, but S. contortus to infraorder Gnathostomatomorpha, and P. terranova to Ascaridomorpha and they differ in morphological features.…”
Section: Discussionmentioning
confidence: 97%